Role of nuclear factor of activated T cells 2 (NFATc2) in allergic asthma. Issue 4 (20th October 2020) - Jakobi, Marielena; Kiefer, Alexander; Mirzakhani, Hooman; Rauh, Manfred; Zimmermann, Theodor; Xepapadaki, Paraskevi; Stanic, Barbara; Akdis, Mubeccel; Papadopoulos, Nikolaos G.; Raby, Benjamin A.; Weiss, Scott T.; Finotto, Susetta
Abstract: Background: We recently described increased NFATc1, IRF4, and NIP45 messenger RNA (mRNA) expression in peripheral blood mononuclear cells (PBMCs) of asthmatic children and adults with multiple allergies. Objective: NFATc2 has been described to associate with IRF4 to induce interleukin‐4, and to be inhibited by T‐bet. Here, we analyzed the role of NFATc2 in asthmatic children and adults. Methods: PBMCs were isolated from the blood of control of asthmatics subjects. Some PBMCs were analyzed untreated and some cultured with and without phytohemagglutinin. Then, RNA was extracted from the cells and cytokines were measured in the supernatants via enzyme‐linked immunosorbent assay or multiplex analysis. RNA was then reverse‐transcribed and NFATc1, NFATC2, IRF4, and T‐bet mRNA were analyzed by real‐time polymerase chain reaction. In addition, in peripheral blood cells, NFATc2 expression was analyzed, in a population of asthmatic children and adults from the Asthma BRIDGE study. Results: In addition to NFATc1 and NIP45, also NFATc2 was found upregulated in PBMCs and peripheral blood cells from asthmatic children and adults with allergic asthma. Moreover, NFATc1 directly correlated with lymphocytes number whereas NFATc2 correlated with peripheral eosinophilia in asthma. Conclusions: In addition to NFATc1 and NIP45, NFATc2 was found upregulated in asthma. Moreover, NFATc1 mRNA correlated with lymphocytes both in control and asthma, and NFATC1 and NFATc2 mRNA showed a direct correlation with eosinophils in controls but not in asthma, indicating that NFATc1 is associated with lymphocytes and not eosinophils in asthma. Clinical Significance: Targeting NFATc2 in T lymphocytes might ameliorate the allergic phenotype in asthmatic subjects. Abstract : In addition to NFATc1 and NIP45, NFATc2 was found upregulated in asthma. Moreover, NFATc1 messenger RNA (mRNA) correlated with lymphocytes both in control and asthma. NFATc2 mRNA showed a direct correlation with eosinophils both in controls and asthma, indicating that NFATc1 is associated with lymphocytes and not eosinophils in asthma.